Ontario Needs a Raise - Macdonald, David (Canadian Centre for Policy Alternatives, Ontario Office, 2017)
The Ontario government has committed to raise its minimum wage to $14 on January 1, 2018 then to $15 on January 1, 2019. This paper examines who in the province will get a "raise" from the $15 minimum wage, and finds it will largely benefit the province’s most marginalized—a broad and diverse swath of workers including contract, seasonal, and casual workers, part-time workers, women, and immigrants. The report also finds that the vast majority of workers who will benefit from a higher minimum wage are over the age of 20, and that they work for big companies (those with 500 or more employees), not small businesses. The study comes as the Ontario government consults the public about its decision to raise the minimum wage to $15 by January 2019. Although the data source for these findings, the Labour Force Survey (LFS) public use microdata file (PUMF), did not specify Indigenous identify, additional research has shown the benefits of a $15 minimum wage to Indigenous Ontarians would be significant, particularly for First Nations women and families. –Website description